Low-Resistivity p-Type Doping in Wurtzite ZnS Using Codoping Method. (19th August 2013) - Li, Deng-Feng; Luo, Min; Li, Bo-Lin; Wu, Cheng-Bing; Deng, Bo; Dong, Hui-Ning
Abstract : By using first principles calculations, we propose a codoping method of using acceptors and donors simultaneously to realize low-resistivity and high carrier concentration p-type ZnS with wurtzite structure. The ionization energy of single N S can be lowered by introducing the II I Zn - N S (III = Al, Ga, In) passivation system. Codoping method in ZnS (2N, III) has lower formation energy comparing with single doping of N since III elements act as reactive codopants.